1961
DOI: 10.1104/pp.36.4.437
|View full text |Cite
|
Sign up to set email alerts
|

The essential role of calcium in selective cation transport by plant cells

Abstract: The mechanisms whereby plant cells absorb inorganic ions from the external media are selective: they discriminate among different ions. Particularly intriguing is the discrimination between potassium and sodium ions. Most plant cells accumulate much higher concentrations of potassium than of sodium ions, even from media in which the sodium concentration greatly exceeds that of potassium.Perhaps the best way to investigate these specificities is to study the manner in which different ions affect each other's ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
200
1
8

Year Published

1962
1962
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(226 citation statements)
references
References 10 publications
17
200
1
8
Order By: Relevance
“…Its importance in the regulation of ion transport is well known (6,26). Its effects on the maintenance of RNA and of protein levels in Lemna have been described by Trewavas (24,25), and these components are considered central indices of senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Its importance in the regulation of ion transport is well known (6,26). Its effects on the maintenance of RNA and of protein levels in Lemna have been described by Trewavas (24,25), and these components are considered central indices of senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Na + has been shown to suppress K + influx in both its high-and low-affinity ranges, particularly at millimolar concentrations (Cheeseman 1982;Jeschke 1982;Schachtman and Schroeder 1994;Rubio et al 1995;Gassmann et al 1996;Maathuis et al 1996;Santa-María et al 1997;Martínez-Cordero et al 2005;Kronzucker et al 2006Kronzucker et al , 2008Nieves-Cordones et al 2007). Some studies have reported only weak Na + effects (Epstein 1961;Epstein et al 1963; see also Seemann and Critchley 1985), or even stimulations of K + influx by Na + (Rubio et al 1995;Spalding et al 1999), but such studies are in the minority. As pointed out earlier in this review, and powerfully by others , some conflicting data on this front most probably arise from differences in experimental approaches, in particular between heterologous expression systems, excised roots, and intact plants (Haro et al 2010).…”
Section: Sodium Toxicitymentioning
confidence: 99%
“…In addition to the competitive effect of Ca on K absorption (19), other stimulatory (3,4,7,11,21) and inhibitory (3, 7,1 1) effects of Ca have also been reported for short-term, excised-root experiments. The stimulatory effects of Ca have been attributed to the need to maintain the integritv of cellular memibranes (14,20) and of selective ion transport mechanisms by which K is actively absorbed (4).…”
mentioning
confidence: 99%